the Application of Financial Management Concepts in Cafe Selection Decision Support Systems Using the SAW Method: Penerapan Konsep Management Keuangan Sistem Pendukung Keputusan Pemilihan Cafe Menggunakan Metode SAW - mauli haspianto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
A Cafe is a place to eat and gather with a more comfortable atmosphere, there are many cafes that exist and are developing in Seruyan district, giving rise to an increase in the economy and the government is expected to be able to help cafes in the Seruyan area, most cafes are managed by young people so that it can have a positive impact if they are in provide support from the government. Therefore the researcher created a decision support system to help related parties to choose the best cafe. This decision support system is designed to provide an objective picture of the cafes in Seruyan. The method used in this study is the SAW (Simple Additive Weighting) method, which is an SPK method used to select various objects that are used as the best alternative from the many existing alternatives, with the criteria used namely location, atmosphere, menu, price, service and cleanliness. With this decision-making system, it is hoped that it can help several parties, such as the tourism office and also the UMKM and industry cooperative services to become a source of reference if you want to develop SMEs and businesses in Seruyan District